Modification of the existing maximum residue level for boscalid in pomegranates. (11th September 2020) - ; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: In accordance with Article 6 of Regulation (EC) No 396/2005, the applicant BASF SE submitted a request to the competent national authority in Greece to modify the existing maximum residue level (MRL) for the active substance boscalid in granate apples/pomegranates. The data submitted in support of the request were found to be sufficient to derive an MRL proposal for pomegranates. Adequate analytical methods for enforcement are available to control the residues of boscalid in the commodity under consideration at the validated limit of quantification (LOQ) of 0.01 mg/kg. Based on the risk assessment results, EFSA concluded that the long‐term intake of residues resulting from the use of boscalid according to the reported agricultural practice is unlikely to present a risk to consumer health. The reliable end points, appropriate for use in regulatory risk assessment are presented.